How COVID-19 Could Change the Economics of the Plastic Recycling Sector - Ibrahim Issifu; Eric Worlanyo Deffor; Ussif Rashid Sumaila (Recycling, 2021)
The price of oil has a great influence on prices of recycled plastics and, therefore, plastic recycling efforts. Here, we analyze the effects of the ongoing COVID-19 pandemic on crude oil price and how this, in turn, is likely to affect the degree of plastic recycling that takes place. Impulse response functions and variance decompositions, calculated from the structural vector autoregression, suggest that changes in crude oil prices are key drivers of the price of recycled plastics. The findings highlight that because plastics are made from the by-products of oil, falling oil prices increase the cost of recycling. Therefore, the price of recycled plastics should be supported using taxes while encouraging sustained behavioral changes among consumers and producers to selectively collect and recycle personal protective equipment so that they do not clog our landfills or end up in our water bodies as plastic waste.